The Gene Catalog and Comparative Analysis of Gut Microbiome of Big Cats Provide New Insights on Panthera Species - Mittal, Parul; Saxena, Rituja; Gupta, Atul; Mahajan, Shruti; Sharma, Vineet K. (Frontiers in Microbiology, 2020)
Majority of metagenomic studies in the last decade have focussed on revealing the gut microbiomes of humans, rodents and ruminants, however the gut microbiome and genic information (gene catalogue) of large felids such as Panthera species is largely unknown till date. In this study, the gut bacterial, fungal and viral metagenomic composition was assessed from three Panthera species (lion, leopard and tiger) of Indian origin, which were consuming the same diet and belonged to the same geographical location. A non-redundant bacterial gene catalogue of the Panthera gut consisting of 1,507,035 putative genes was constructed from 27 Panthera individuals, which revealed a higher abundance of purine metabolism genes correlating with their purine-rich dietary intake. Analysis with CAZy and MEROPS databases identified enrichment of glycoside hydrolases, glycoside-transferases, and collagenases in the gut, which are important for nutrient acquisition from animal biomass. The bacterial, fungal and viral community analysis provided the first comprehensive insights into the Panthera-specific microbial community. The Panthera gene catalogue and the largest comparative study of the gut bacterial composition of 68 individuals of Carnivora species from different geographical locations and diet underscores the role of diet and geography in shaping the Panthera gut microbiome, which is significant for the health and conservation management of these highly endangered species.